Cytotoxicity effect of oil palm (Elaeis guineensis) kernel protein hydrolysates - Chang, Sui Kiat; Hamajima, Hiroshi; Ismail, Amin; Yanagita, Teruyoshi; Mohd Esa, Norhaizan; Baharuldin, Mohamad Taufik Hidayat (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
This study was conducted to ascertain the cytotoxicity effect of oil palm (Elaeis guineensis) kernel protein hydrolysates (OPKHs) produced from its protein isolate. A modified microplate titer WST-1 [2-(4-iodophenyl)-3-(4-nitrophenyl)-5-(2,4-disulfophenyl)-2H-tetrazolium] assay was used to investigate the cytotoxicity of hydrolysates produced from protease and pepsin-pancreatin hydrolysis at various concentrations (0.1, 1, 10, 100 μg/ml and 1 mg/ml) using HepG2 cell model. Additionally, peptide stimulation test using OPKHs at 1 mg/ml was carried out to investigate whether OPKHs could serve as growth factor for HepG2 cells other than affecting its viability. As a result, oleic acid appeared to normalize the WST-1 readings of HepG2 cells treated with both hydrolysates at 1 mg/ml. The presence of amino acids in OPKHs could stimulate the growth and prolongs the viability of HepG2 cells. Both OPKHs were non-cytotoxic to HepG2 cells at all tested concentrations even at high concentrations. This study indicated that pepsin-pancreatin and protease hydrolysates produced from oil palm kernel protein were non-cytotoxic on HepG2 cells.